Down a Rabbit Hole: How Prior Media Consumption Shapes Subsequent Media Consumption - Woolley, Kaitlin; Sharif, Marissa A. (Journal of Marketing Research, 2022)
Consumers often become “stuck in a rabbit hole” when consuming media. They may watch several YouTube videos in the same category or view several thematically similar artistic images on Instagram in a row, finding it difficult to stop. What causes individuals to choose to consume additional media on a topic that is similar to (vs. different from) what they just experienced? The authors examine a novel antecedent: the consecutive consumption of multiple similar media. After viewing multiple similar media consecutively, more consumers choose to (1) view additional similar media over dissimilar media or (2) complete a dissimilar activity entirely, even when the prior consumption pattern is externally induced. The rabbit hole effect occurs because of increased accessibility of the shared category: when a category is more accessible, people feel immersed in it and anticipate that future options within that category will be more enjoyable. The authors identify three characteristics of media consumption that contribute to the rabbit hole effect by increasing category accessibility: similarity, repetition, and consecutiveness of prior media consumption. This research contributes to literature on technology, choice, and variety seeking, and it offers implications for increasing (vs. slowing) similar consumption.